Hardness measurements of different types of metal using vickers and brinell hardness testing method - Fazlan Mohammad Ali, 1988-; Zuhairi Ibrahim,lcsupervisor; Fakulti Sains (2010)
Project paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2010